2021
DOI: 10.3390/computers10120158
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Deep Learning Algorithms for PPG Signal Processing and Classification

Abstract: Photoplethysmography (PPG) is widely used in wearable devices due to its conveniency and cost-effective nature. From this signal, several biomarkers can be collected, such as heart and respiration rate. For the usual acquisition scenarios, PPG is an artefact-ridden signal, which mandates the need for the designated classification algorithms to be able to reduce the noise component effect on the classification. Within the selected classification algorithm, the hyperparameters’ adjustment is of utmost importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Some other approaches include waveform morphology analysis combined with a decision-tree classifier (Sukor et al 2011), developing an artifact detector on the PPG signal (Robles-Rubio et al 2013), or constructing a PPG signal quality index based on features derived by the signal (Orphanidou et al 2014, Zanon et al 2020. Esgalhado et al (2021) proposed a CNN-LSTM classifier for PPG signal quality classification and reported accuracy of 89.4% (i.e. 3% lower than our best reported accuracy).…”
Section: Related Workmentioning
confidence: 82%
“…Some other approaches include waveform morphology analysis combined with a decision-tree classifier (Sukor et al 2011), developing an artifact detector on the PPG signal (Robles-Rubio et al 2013), or constructing a PPG signal quality index based on features derived by the signal (Orphanidou et al 2014, Zanon et al 2020. Esgalhado et al (2021) proposed a CNN-LSTM classifier for PPG signal quality classification and reported accuracy of 89.4% (i.e. 3% lower than our best reported accuracy).…”
Section: Related Workmentioning
confidence: 82%
“…Regarding the window type, it has been shown that Hamming and Kaiser's windows are good options for generating spectrograms from pulse wave signals such as PPG (Zong and Jafari, 2015;Esgalhado et al, 2021). Overlapping percentage values of 0, 60, and 95 for Hamming windows and 0, 61, and 70 for Kaiser, were selected based on the values reported in (Trethewey, 2000) and (Heinzel et al, 2002).…”
Section: Spectrogram Generationmentioning
confidence: 99%
“…PPG sensors are widely employed in wearable devices [ 5 , 6 ]. PPG sensors emit infrared rays to the skin and measure the amount of blood flow by determining the amount of rays absorbed in red blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…The DeepCNAP model for heart rate measurement using PPG signals was presented [ 14 ]. A deep learning model for robust PPG wave detection was proposed in [ 5 ]. The best performing model was a CNN-long short-term memory (LSTM) algorithm with a PPG synchro-squeezed Fourier transform (SSFT) and the accuracy, precision, and recall were 0.894, 0.923, and 0.914, respectively.…”
Section: Introductionmentioning
confidence: 99%